(Measuring unemployment rates in Libya: an applied study on the Libyan economy during the period (1962-2012 - Al Jeroushi, Ali Abdul Salam; Arbab, Musab Mutasem Saeed (Journal of Economic, Administrative and Legal Sciences, 2017)
This research aimed to measure the real unemployment rate in the Libyan economy, during the Period from (1962-2012). The research also aimed to identify any manifestation of disguised unemployment rate in the Libyan economy. To achieve the research objective, the research sought to investigate the concept of unemployment in the official meaning, which, really reflects the open unemployment, as well as the concept of unemployment in scientific terms, which, on the other hand, reflects the real unemployment. The research also aimed to examine the methodology of the measurement of the real unemployment rate, as well as the evolution of its concept, in addition to some economic changes relating thereto, during the period in research question. The research used both the analytical descriptive approach and the statistical analysis method and the mathematical method in measuring the real unemployment rate in the Libyan economy during the period from (1962-2012). The research findings have shown that, both rates of open unemployment (actual unemployment) and real unemployment in the Libyan economy are significantly rising. The research findings have also shown the fact that, the most part of the reasons behind the real unemployment, is the decrease in the levels of productivity of the labor element, which in turn indicates the existence of disguised unemployment manifestation in the Libyan economy. The research then concluded with a set of recommendations, including the prequalification of graduates and those whose educational qualifications do not consist with the requirements of the labor market.